Quality Physical Intervention Activity for Persons with Down Syndrome - Meir Lotan (The Scientific World Journal)
Persons with Down syndrome (DS) are at risk for a life of inactivity that can result in a multitude of medical problems including heart and vascular diseases. This review presents findings regarding the physical status of individuals with DS, as well as proper interventions found to improve the physical fitness and general health for this population. This review was written with the intent to suggest practical directions in planning and implementing quality physical intervention programs for this population.